PRACTICAL INTERFERENCES IN THE EVOLUTION OF DENTAL PROSTHETICS - Crețu Cosmin – Ionuț; Tibeică Andreea; Curcă Răzvan; Orghidan Cristian; Ulman Cosmin; Iacob Andrei; Agop-Forna Doriana; Norina Forna (Romanian Journal of Oral Rehabilitation)
The field of dental prosthetics has undergone significant evolution due to advances in materials, technology, and patient-specific customization. Practical interferences, such as technological limitations, material constraints, and clinical challenges, continue to influence the trajectory of this field. This paper aims to analyze these interferences, highlighting their impact on the design, production, and clinical application of dental prostheses. By reviewing existing literature and case studies, this work identifies key obstacles and proposes strategies for overcoming them. The findings underscore the need for interdisciplinary collaboration, continuous research, and technological investment to address these interferences effectively.